Crotalarieae and Genisteae of the South African Great Escarpment are nodulated by novel Bradyrhizobium species with unique and diverse symbiotic loci - Beukes, Chrizelle W.; Stępkowski, Tomasz; Venter, Stephanus N.; Cłapa, Tomasz; Phalane, Francina L.; le Roux, Marianne M.; Steenkamp, Emma T. (Molecular phylogenetics and evolution, 2016)
[Display omitted] •Isolated 21 rhizobial isolates, corresponding to seven Bradyrhizobium species.•One of these is conspecific with B. arachidis, while the others are new.•Most of the isolates formed part of new nodA clades (Clades XIV and XV).•Similar groupings were recovered from the nifD genealogy.•Evolution of these rhizobia is subject to environmental factors and host distribution. The genus Bradyrhizobium contains predominantly nitrogen-fixing legume symbionts. Phylogenetic analysis of the genes responsible for their symbiotic abilities (i.e., those encoded on the nodulation [nod] and nitrogen-fixation [nif] loci) has facilitated the development of an extensive phylogeographic framework for the genus. This framework however contains only a few nodulating isolates from Africa. Here we focused on nodulating Bradyrhizobium isolates associated with native southern African legumes in the tribes Genisteae and Crotalarieae found along the Great Escarpment in the Mpumalanga Province of South Africa. The aims of this study were to: (1) obtain rhizobial isolates from legumes in the Genisteae and Crotalarieae; (2) verify their nodulation ability; (3) characterize them to species level based on phylogenetic analyses of several protein coding gene regions (atpD, dnaK, glnII, recA, rpoB and gyrB) and (4) determine their placement in the phylogeographic framework inferred from the sequences of the symbiotic loci nodA and nifD. Twenty of the 21 Bradyrhizobium isolates belonged to six novel species, while one was conspecific with the recently described B. arachidis. Among these isolates, the nodA phylogeny revealed several new clades, with 18 of our isolates found in Clades XIV and XV, and only three forming part of the cosmopolitan Clade III. These strains formed predominantly the same groups in the nifD phylogeny although with slight differences; indicating that both vertical and horizontal inheritance of the symbiotic loci occurred. These findings suggest that the largely unexplored diversity of indigenous African rhizobia are characterized by unique ancestries that might mirror the distribution of their hosts and the environmental factors driving their evolution.